Pengaruh Kualitas Pelayanan terhadap Kepuasan Pasien pada Rumah Sakit Sari Asih di Wilayah Ciamis - Saptaning Ruju Paminto; Endah Lisarini; Hasbu Naim Syaddad (Jurnal Tadbir Peradaban, 2021)
This study aims to determine the effect of Service Quality on Patient Satisfaction at Sari Asih Hospital in Ciamis Region. The method used is explanatory research with a sample of 96 respondents. The analysis technique uses statistical analysis with regression testing, correlation, determination and hypothesis testing. The results of this research variable Service Quality obtained an average score of 3.409 with good criteria. Patient Satisfaction Variable obtained an average score of 3,831 with good criteria. Service quality has a significant effect on patient satisfaction with the regression equation Y = 9.311 + 0.851X, and a correlation value of 0.774 or strong with a determination of 59.9%. Hypothesis testing obtained a significance of 0.000 <0.05.